The Role of CSR in the Corporate Identity of Banking Service Providers - Pérez, Andrea; Rodríguez del Bosque, Ignacio (2012)
The study here is a qualitative research based on multiple case studies of banking service providers to analyze the role of corporate social responsibility (CSR) in the definition of the corporate identity of these kinds of organizations. The results show that, although companies increasingly integrate CSR into their business strategies, there are some aspects of its management such as its communication or the measurement of its results that detract from its success. These results have important implications for those managers pursuing an effective management of CSR policies and strategies in their organizations, especially as the information comes from 6 of the biggest and most important banking institutions in a European country, with a declared assets (loans) volume which represents 62.75% of the total assets in the national banking industry, and thus largely representing the possible heterogeneity of the market in terms of company size, location, legal status, and management styles.
Keywords: Banking Industry; Case study; corporate communication; Corporate Social Responsibility; Corporate Identity; Corporate image